Instagram’s utilization and advertising performance on viral product consumption for millennials - Istiyana Afifah (Jurnal Sosiologi Dialektika, 2022)
The popularity of Instagram gave rise to new celebrities with the name of Instagram celebrities. Instagram celebrities are individuals who have a popularity for other Instagram users, the blue tick icon as a sign that the account is owned by a popular individual. There is a role of Instagram celebrities in introducing products to the millennial generation. In addition, Instagram celebrities can form new fashions or trends in the millennial generation. Instagram celebrities can be a reference for millennials to decide to buy a product. The study used qualitative methods and interpretive approaches. The criteria of informants are to use Instagram social media and know Mahika Kids and Ngikan Yuk products. Data collection techniques use primary data and secondary data. This study found that viral products arise from the delivery of advertising messages through Instagram in the form of objects that can be events, there are simulations of ads that become a topic of conversation for millennials, and Instagram celebrities become references for millennials in assessing and interpreting a product. The decision of millennials to buy viral products is the desire to show a symbol of self-existence that can follow new trends and advertising performance from Instagram celebrities that attract millennials.